The Mother Goose diaries - Colfer, Chris (London: Little, Brown Books for Young Readers, 2015)
Mother Goose's diary entries over the last five hundred years take listeners on a journey to learn buried secrets. Mother Goose has had centuries of adventure and finally she's allowing you - her favourite reader - to take a peek at all her secrets. Who else gossiped with Queen Elizabeth I, taught geography to Napoleon, marched for equal rights with Martin Luther King, Jr. and served as Andy Warhol's muse? Open these pages and come on a journey through time ... are you ready?
Keywords: Children's stories